Environment and Geochemistry of Sediments (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint considers a vast range of questions devoted to environmental geochemistry. The themes of the research cover different problems of the geochemistry of sediments, such as the reconstruction of the paleoenvironment in the lake basins, climate evolution during the Late Carboniferous–Early Permian period, and the study of the paleoenvironment in the eastern Tethys. Several articles discuss the features of the geochemistry of sedimentation in places of prehistoric anthropogenic activity. Based on the geochronological analysis, the magnetic susceptibility anthropogenic sources of metals in south-eastern Baltic lake sediments from the Neolithic to the Medieval Age were determined. A new approach using the geochemical indication was developed for the determination of the functional zones of prehistoric archaeological sites in Eastern Europe. The application of geochemical multi-element and geochronological analyses of the Iron Age and early Roman cultural layers was considered at the archaeological site in the Netherlands. Some papers are devoted to the pollution hazard problem concerning, for example, the accumulation and distribution of a hazardous contaminant, mercury (Hg), in the basin of Onega Lake, Russia, the second largest lake in Europe, and the distribution of arsenic in the soils of the Verkhnekamskoe potassium salt deposit, Perm Krai, Russia. The ecological state of basins as a result of technogenic processes using a geochemical approach is illuminated in the papers devoted to the mineralogical and geochemical contents of the bottom sediments of Al-Kharrar and Al-Shuaiba Lagoons, Red Sea, Saudi Arabia.